REPRESENTAÇÕES SOCIAIS DO SUICÍDIO PARA BOMBEIROS MILITARES E COMUNITÁRIOS DE UMA CIDADE DO PLANALTO NORTE CATARINENSE - Thais Eduarda Pereira Staudt (2023)
This research aimed to analyze the social representations of suicide for Military and Community Firefighters in a city in the North Plateau of Santa Catarina. Interviews were conducted with 14 firefighters, ten military and four community, in which we sought to explore the ways of thinking, feeling and acting of these workers in the face of suicide attempts and, also, the way they build their social representations about the phenomenon. The interviews were recorded, transcribed and analyzed using Content Analysis. The results indicate that suicide is represented as a mental problem, of a religious nature, related to the causes of what would lead a person to commit suicide, as well as its unpredictability. In addition, it was possible to perceive that these representations are anchored in what it is to be a firefighter, that is, in the identification of the subject with the profession, in which dedication, self-denial, empathy and heroism stand out as the main guiding principles of action in the face of an occurrence. of attempted suicide. It should be noted that this research has limitations, as it is restricted to a specific group of military and community firefighters who are part of the Military Fire Department of the State of Santa Catarina, as well as the region of the North Plateau of Santa Catarina. Furthermore, the need for investment in studies and strategies aimed at guiding the work of firefighters is highlighted, as well as in the construction of actions that allow the reception and listening to their experiences in the face of these occurrences.